Rivalry or alliance?: the relationship between hyperbole and literal language - Cano Mora, Laura (Epos : Revista de filología, 2013)
This paper focuses on the relationship between neighbouring literal and figurative expressions, a much under-researched area in figurative language theories. Traditionally it has been assumed that language is used figuratively when a literal expression would be inadequate, thus supporting the view that figurative and literal language replace or substitute each other. In order to question this view and to explore this relationship, a group of hyperbolic adverbs extracted from the British National Corpus and used in naturally-occurring speech was examined. The results show that hyperbole and literal comments seem to extend and complement, rather than replace, each other. This complementation is often achieved through paraphrase or clarification of a preceding remark, whether literal or exaggerated. The analysis also seems to suggest that if speakers need to add some information the most common pattern is a hyperbole followed, rather than preceded, by a literal expression. El presente artículo se centra en el estudio de la relación entre expresiones literales y figuradas adyacentes, cuestión rara vez investigada en las teorías del lenguaje figurado. Tradicionalmente se ha creído que los hablantes utilizamos las figuras cuando el lenguaje literal resulta inadecuado, reafirmando así la idea de que el lenguaje literal y figurado se sustituyen el uno al otro. Con el fin de cuestionar esta visión y explorar dicha relación examinamos un grupo de adverbios hiperbólicos usados en conversaciones reales extraídas del British National Corpus. Los resultados indican que la hipérbole y el uso literal del lenguaje parecen complementarse en lugar de reemplazarse. Con frecuencia dicha complementariedad se consigue a través de la paráfrasis o clarificación de un comentario previo, ya sea literal o exagerado. El análisis a su vez parece sugerir que cuando el hablante siente la necesidad de añadir información el patrón más común es una hipérbole seguida, en lugar de precedida, de una expresión literal.